Maternal awareness regarding vitamin D supplementation and its deficiency among their infants in a tertiary care hospital, Puducherry: a cross-sectional study - Harivignesh R.; Amarnath; Rajini S. (International Journal Of Community Medicine And Public Health, 2026)
Background: Vitamin D deficiency is a common public health problem affecting mothers and infants, even in sun-rich countries like India. Maternal awareness plays a key role in preventing deficiency and its complications in infants. This study aimed to assess maternal awareness regarding vitamin D supplementation and its deficiency among infants, and to determine the association with sociodemographic factors. Methods: A hospital-based cross-sectional study was conducted among 200 postnatal mothers attending the Paediatrics OPD of a private medical college in Puducherry from September to December 2025. Participants were selected using systematic random sampling. Data were collected using a pre-tested, self-administered questionnaire via an online platform. Descriptive statistics were expressed as frequencies and percentages, and associations were tested using the Chi-square test (p